DIABETES MELLITUS AND COVID-19. CARDIOVASCULAR COMPLICATIONS AND COURSE OF TYPE 2 DIABETES MELLITUS AFTER CORONAVIRUS INFECTION - D.K, Najmutdinova; D.A , Urunbayeva; N.G, Sadikova; S.A, Pulotova (Journal of Medical Genetics and Clinical Biology, 2024)
The COVID-19 pandemic, caused by the coronavirus SARS-CoV-2, has had profound effects on global health and economics since its emergence in late 2019. Over 770 million confirmed cases of COVID-19 have been reported worldwide, with millions of deaths attributed to the virus. Studies have shown that individuals with T2DM are at a higher risk of severe illness and mortality if they contract COVID-19. The presence of diabetes, especially when poorly controlled, can exacerbate the inflammatory response to the virus. Patients with T2DM often have comorbidities such as cardiovascular disease, hypertension, and obesity, which further increase the risk of severe COVID-19 complications